University lecturers’ preparedness to use technology in teacher training of mathematics during COVID-19: The case of Ethiopia - Machaba, F.; Bedada, T. (South African Journal of Higher Education, 2022)
The study aimed to investigate Ethiopian university lecturers’ readiness to use technology for teaching mathematics at the tertiary level during the COVID-19 pandemic when they were compelled to adapt to distant education. Using Google Forms, online questionnaires were distributed to 41 lecturers in three Ethiopian universities, of whom eighteen participated. Before the research, the questionnaire was piloted with eight lecturer participants to categorise questions and validate the instrument using the Rasch measurement model. The questionnaire was locally developed based on guidelines from the literature. It purposed to investigate university lecturers’ individual preparedness for technological instruction in terms of their knowledge, beliefs and current, and historical exposure to this mode of instruction. As a counterbalance, some circumstantial factors influencing their readiness were investigated too. Lecturers’ optimistic beliefs about using educational technologies have been found to contrast with some disabling circumstantial factors. This study revealed that the lecturers were generally able and interested in integrating technology into the teaching process but that barriers, primarily at the institutional level, hindered them from doing so. In addition to the technologies suggested in the questionnaire, participants enriched the research findings by adding more possible technologies that lecturers may use for educational purposes. The data was analysed using WINSTEPS (Student Version of WINSTEPS 4.7.0.0) and SPSS version 20. The results showed the reliability of using the instrument was 0.77 based on Cronbach’s alpha. The PT-measure correlation value determined the construct validity (PMC), ranging from 0.23 to 0.71 except item PUT15’s infit and outfit MNSQ between 0.1 to 1.86 and ZSTD range -1.05 to 1.61, which was acceptable. The fit statistics showed that the person separation index, 1.97, was considered good and that the item separation index, 0.63 was within an acceptable range. Person and item reliability were at 0.8 and 0.28, respectively. The result indicated that the new instrument with five items after eliminating unfit items (such as items FAT19, PTT10, KDT1, PTT8 and PTT 12) was reliable and valid to measure the use of technology in the teaching and learning process of the university lecturers.